2009
DOI: 10.1016/j.foodchem.2008.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbon dioxide fluid extraction of Hibiscus cannabinus L. seed oil: A potential solvent-free and high antioxidative edible oil

Abstract: The supercritical fluid extraction (SFE) trends and antioxidant activities of Hibiscus cannabinus seed oils were studied. SFE results indicate that extraction pressure is the major factor determining the oil yield. In comparison, classic Soxhlet extraction (SOX/L) yielded higher oil content than SFE (P < 0.05). However, no significant differences in oil content were observed in SFE at 600 bars/80 °C, rapid Soxhlet extraction (SOX/S) and conventional ultra-sonic assisted solvent extraction (SONIC) (P > 0.05). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 19 publications
2
72
2
Order By: Relevance
“…Earlier study has shown that kenaf seed oil might actually possess better antiradical activity if compared with some commercial edible oils (canola oil, corn oil and so on) and it can potentially serve as high antioxidative edible oil. Compared with this study, the IC 50 value for tomato seed oil was 1590 µg/mL, only about 13% of that of kenaf seed oil, 12270 µg/mL (Chan and Ismail, 2009). This result showed that the tomato seed oil might actually possess better antiradical activity if compared with kenaf seed oil and it can potentially serve as a high antioxidative edible oil.…”
Section: Resultscontrasting
confidence: 83%
“…Earlier study has shown that kenaf seed oil might actually possess better antiradical activity if compared with some commercial edible oils (canola oil, corn oil and so on) and it can potentially serve as high antioxidative edible oil. Compared with this study, the IC 50 value for tomato seed oil was 1590 µg/mL, only about 13% of that of kenaf seed oil, 12270 µg/mL (Chan and Ismail, 2009). This result showed that the tomato seed oil might actually possess better antiradical activity if compared with kenaf seed oil and it can potentially serve as a high antioxidative edible oil.…”
Section: Resultscontrasting
confidence: 83%
“…In a previous study (Chan and Ismail 2009), our group showed that using the extraction pressure 600 bars and temperature of 40°C gave a high yield of oil extraction for Hibiscus cannabinus using SFE. Depending on that result we used 600/40 extraction parameters for the extraction of the cantaloupe oil.…”
Section: The Total Oil Content Of C Cantalupensis and C Reticulatesmentioning
confidence: 93%
“…In addition, carbon dioxide is both non-toxic and non-explosive and its use can reduce the consumption of organic solvents; this is especially useful for the production of natural products used in foods and pharmaceuticals [2]. Supercritical carbon dioxide (SC-CO 2 ) has been successfully used for the extraction of oils from oil seeds including parsley seed [1], cottonseed [3], palm kernel [4] and kenaf seed [5].…”
Section: Introductionmentioning
confidence: 99%